Effect of using PCC fillers and nanocellulose on pulp and paper properties - Hamid reza Rodi (Regional Information Center for Science and Technology (RICeST), 2018)
In this research, the effect of adding precipitated calcium carbonate filler combined with nanocellulose as reinforcement was examined to compensate the strengths loss of papers made of bagasse pulp. About 2 % of nanocellulose based on oven dry fibers suspended in water with 0.1 % consistency homogenized by ultrasonic was added to the pulp having 15 % PCC filler and was compared with the same sample without nanocellulose and base pulp (without any additives). Cationic polyacrylamide retention agent was added to the pulp suspension at the constant level of 0.14 % based on oven dry fibers. Statistical analysis of results revealed that the drainage time increased by adding of PCC and nanocellulose system to the bagasse pulp suspension. Addition of nanocellulose has enlarged filler particle retention due to the formation of adhesive flocs. Prepared SEM images from paper samples confirm filler particles flocculation, larger filler retention and their better distribution in paper network. Moreover, in papers filled by PCC and nanocellulose with roughly equal similar opacity and brightness, loss of strength characteristics due to adding of filler has been compensated. Although relatively higher drainage time of this pulp suspension is a substantial limitation, but pretreatment of filler with nanocellulose prior to its addition to the pulp can be investigated as a promising alternative.